Modulation of Democracy: Partisan Communication During and After Election Campaigns - Bruno Castanho Silva; Lennart Schürmann; Sven-Oliver Proksch (British Journal of Political Science, 2024)
It is well known that politicians speak differently when campaigning. The shadow of elections may affect candidates' change in tone during campaigns. However, to date, we lack a systematic study of the changes in communication patterns between campaign and non-campaign periods. In this study, we examine the sentiment expressed in 4.3 million tweets posted by members of national parliaments in the EU27 from 2018 to 2020. Our results show that (1) the opposition, even populists and Eurosceptics, send more positive messages during campaigns, (2) parties trailing in the polls communicate more negatively, and (3) that the changes are similar in national and European elections. These findings show the need to look beyond campaign times to understand parties' appeals and highlight the promises of social media data to move beyond traditional analyses of manifestos and speeches.
https://doi.org/10.7910/DVN/DNUXY9
Keywords: 320; European politics; text analysis; social media; legislative behaviour; sentiment analysis